Rapid Progression of Red Itchy Rash, Diagnostic Dilemma - Keyal, Uma; Aryal, Gopi; Shrestha, Sanju Babu; Bhatta, Anil Kumar (Nepal Journal of Dermatology, Venereology & Leprology, 2023)
Cutaneous T-cell lymphoma (CTCL) is an uncommon type of cancer that begins in white blood cells called T lymphocytes (T cells). Normally, T cells help body's immune system to fight off infection but, in CTCL, these cells develop abnormalities that make them attack the skin. It comprises heterogeneous group of skin neoplasms, the most common being mycosis fungoides (MF). Skin lesions are classified into patches, plaques, and tumor stage. Extra skin manifestations like enlarged lymph nodes are usually seen in plaques or tumor stage, when there are thick lesions on skin. It is usually a slow growing cancer that develops over many years. Herein, we present an 83-year female patient who suddenly developed extremely itchy patches on abdomen, which had spread to involve the entire trunk and all four limbs in about 10 days’ time. She already had lymphadenopathy and splenomegaly at the time of presentation. Skin biopsy and immunohistochemistry revealed CD4+ T cells CTCL. Moreover, bone marrow was hypercellular for age with 12% atypical lymphocytes. It is very unusual for CTCL to involve bone marrow at patch stage with no any plaques or nodules on the skin. Also, the sudden onset of skin lesions and its rapid progression with probably, the involvement of lymph nodes and spleen warrant further studies to guide diagnostic approaches and treatment recommendations for CTCL